(untitled) (Bangladesh Journal of Botany, 2018)
Multivariate analysis using two-way indicator species analysis (TWINSPAN) and Canonical correspondence analysis (CCA) were used to classify the phytosociology of the District Vehari, Pakistan. A total of 35 plant species belonging to 23 families were recorded. The first level TWINSPAN divided the vegetation of entire study area into two major communities which were subsequently separated into subcommunities. Each major and sub-community was named following the most important dominant species. CCA identified the relationship of vegetation structure to specific environmental factors. This relationship was studied by CANOCO analysis. In the CCA of all the species for Vehari, soil pH and water pH and EC were the most important variables influencing the species distribution. This survey offers key information regarding vegetation and would be helpful for the conservation of biodiversity of the area under study.